Assessment of Joint Improvised Explosive Device Defeat Organization (JIEDDO) Training Activity - Martin, Brad (RAND Corporation, 2013)
The Joint Improvised Explosive Device Defeat Organization (JIEDDO) carries out training activities both as part of its equipment and system development responsibilities and its responsibility to "train the force" in IED threats and countermeasures. This report assesses whether JIEDDO's programs and functions may be duplicative with those of the military Services, U.S. Special Operations Command, and other agencies.